2020
DOI: 10.1038/s41590-020-0744-z
|View full text |Cite
|
Sign up to set email alerts
|

Follicular helper T cell profiles predict response to costimulation blockade in type 1 diabetes

Abstract: Follicular helper T cells (Tfh) are implicated in type 1 diabetes (T1D) and their development has been linked to CD28 costimulation. We tested whether Tfh were decreased by costimulation blockade using the CTLA-4-Ig fusion protein (Abatacept) in a mouse model of diabetes and in individuals with new onset T1D. Unbiased bioinformatic analysis identified that ICOS + Tfh, and other ICOS + populations including T-peripheral helper cells, were highly sensitive to costimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 51 publications
2
58
0
Order By: Relevance
“…By contrast, CD28 expression was only marginally detected across all perturbations, suggesting that CD28 signaling alone is sufficient for its internalization from the surface. Consistent with its known role as an inducible co-stimulatory molecule 45, 46 , we also found that CD278 ( ICOS ) expression could be promoted and sustained with intact CD28 signaling, independent of effective CD3E stimulation ( Fig. 6c ).…”
Section: Resultssupporting
confidence: 83%
“…By contrast, CD28 expression was only marginally detected across all perturbations, suggesting that CD28 signaling alone is sufficient for its internalization from the surface. Consistent with its known role as an inducible co-stimulatory molecule 45, 46 , we also found that CD278 ( ICOS ) expression could be promoted and sustained with intact CD28 signaling, independent of effective CD3E stimulation ( Fig. 6c ).…”
Section: Resultssupporting
confidence: 83%
“…Though critical for generating appropriate B‐cell responses to infection and vaccination, dysregulated Tfh cell responses can occur and are associated with a variety of autoimmune and inflammatory disorders, many of which develop with increasing age. This suggests that age can impact Tfh cell development and/or function (Blanco et al, 2016; Deng et al, 2019; Edner et al, 2020; Qin et al, 2018; Vinuesa et al, 2016). In mice, age‐dependent changes in CD4 + T cells have been shown to contribute to the defective GC and antibody responses (Eaton et al, 2004; Lefebvre et al, 2016; Maue & Haynes, 2009; Yang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to MS, an increase in circulating T FH cells has been associated with type 1 diabetes (165)(166)(167). A recent study showed that abatacept was able to decrease T FH cells in a mouse model of type 1 diabetes, even after the disease is established (134). Furthermore, abatacept reduces circulating T FH cells in RA and in Sjögren's syndrome (168,169).…”
Section: Targeting T Fh Cells Via Cd28 and Icosmentioning
confidence: 98%
“…T FH cells are broadly identified as CXCR5 + PD-1 + BCL6 + ICOS + and their effector function is primarily associated with the secretion of IL-21 (91). This subset is most strongly linked to GC B cell responses and has only recently been included as a diseaserelevant subset in MS and other disease conditions (133,134). T FH cells have been associated with RA, SLE, and Sjögren's syndrome in a manner dependent on their ability to support GC B cell responses (135).…”
Section: T Fh Cells: Hurting More Than Helping?mentioning
confidence: 99%